Analisis Penerapan Alokasi Dana Desa Dalam Upaya Meningkatkan Pembangunan Desa (Studi Kasus Pada Desa Limau Manis Kecamatan Tanjung Morawa) - shara, yuni; ovami, Debbi chyntia (Jurnal Akuntansi Bisnis Eka Prasetya : Penelitian Ilmu Akuntansi, 2020)
This study aims to analyze the application of the Village Fund Allocation (ADD) in an effort to increase development in the Limau Manis Village, Tanjung Morawa District, Deli Serdang Regency. Data collection methods used in this research are literature study and field study. Furthermore, the results of the study were analyzed through a qualitative descriptive analysis method in which to obtain a picture in understanding and explaining the application of village fund allocations in an effort to increase development in Desa Limau Manis. The data used in this study are primary data with the subject of research is the Limau Manis Village Office of Tanjung Morawa District. The results showed that the application of the Village Fund Allocation (ADD) in an effort to increase development in Limau Manis Village, Tanjung Morawa Sub-District, Deli Serdang District had been running but the allocation was not right on target, this can be seen from the realization of the allocation of village funds that were used for social purposes had less value the remainder is for village government income and other benefits.